Coronavirus Disease in Pakistan: Response and Challenges from Prevention to Care - Naqvi, Syeda Ghadeer Zehra; Fatima, Kainat; Jamal, Kanwal; Sheroze, Muhammad Waqaruddin (Jour Med Resh and Health Sci, 2020)
Immensely contagious Coronavirus disease was imported in Pakistan and became health emergency concern in no time. Pakistan, being a resource limited nation has encountered worst transmission dynamics and received public, social, economic challenges. Pakistani officials responded sufficiently to outbreak. However, community transmission became an emergent threat and proportion of mortalities became exponential. Hence, Pakistan was scantily prepared to respond to an overhanging hazardous outbreak. This study comment on response of Pakistani government to Coronavirus disease, sheds light on challenges faced during the Covid-19 pandemic and concluded by highlighting concept of preparedness and providing some recommendations.